Extension of a reduced entropic model of electron transport to magnetized nonlocal regimes of high-energy-density plasmas. (20th June 2016) - Del Sorbo, D.; Feugeas, J.-L.; Nicolaï, Ph.; Olazabal-Loumé, M.; Dubroca, B.; Tikhonchuk, V.
Abstract: Laser-produced high-energy-density plasmas may contain strong magnetic fields that affect the energy transport, which can be nonlocal. Models which describe the magnetized nonlocal transport are formally complicated and based on many approximations. This paper presents a more straightforward approach to the description of the electron transport in this regime, based on the extension of a reduced entropic model. The calculated magnetized heat fluxes are compared with the known asymptotic limits and applied for studying of a magnetized nonlocal plasma thermalization.